A sandwich structure P (VDF-CTFE) composite film and preparation method thereof

By adopting a sandwich-structured P (VDF-CTFE) composite film, the combination of BNNSs and PMMA layers is used to solve the problem of easy breakdown of existing dielectric materials under high electric fields, and high dielectric constant, low dielectric loss and good high voltage resistance are achieved.

CN114103336BActive Publication Date: 2025-04-08ZHEJIANG UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202010885942.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-08-28
Publication Date
2025-04-08
Estimated Expiration
2040-08-28

AI Technical Summary

Technical Problem

Existing dielectric materials are prone to breakdown under high electric fields, and the aggregation of high content of inorganic nanoparticles weakens the toughness and mechanical properties of polymer-based composites, affecting their widespread use.

Method used

A P (VDF-CTFE) composite film with a sandwich structure consisting of two BNNSs/P (VDF-CTFE) film layers and a PMMA layer sandwiched between them. By electrostatic adsorbing the copolymer HBPE-g-PMMA, the BNNSs are uniformly dispersed and arranged in an orientation manner, combining the electrical insulation of the PMMA layer, the dielectric properties and high voltage resistance of the material are improved.

Benefits of technology

The dielectric constant and energy density of the composite material are significantly improved, while maintaining low dielectric loss and good flexibility, delaying electrical breakdown under high voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0002655581390000011
    Figure HDA0002655581390000011
  • Figure HDA0002655581390000012
    Figure HDA0002655581390000012
  • Figure HDA0002655581390000013
    Figure HDA0002655581390000013
Patent Text Reader

Abstract

The present application discloses a sandwich structure P (VDF-CTFE) composite film and a preparation method thereof. The sandwich structure P (VDF-CTFE) composite film includes two BNNSs / P (VDF-CTFE) film layers and a PMMA layer sandwiched therebetween; in the BNNSs / P (VDF-CTFE) film layer, the surface of the BNNSs is adsorbed with a copolymer HBPE-g-PMMA by electrostatic force, and the BNNSs are uniformly dispersed in the P (VDF-CTFE) and arranged in an oriented manner; the mass ratio of the BNNSs to the P (VDF-CTFE) is 0.1-1wt%; the thickness of the BNNSs / P (VDF-CTFE) film layer is between 5 and 20 μm, and the thickness of the PMMA layer is between 0.5 and 5 μm. The sandwich structure P (VDF-CTFE) composite film prepared by the present invention has a high dielectric constant, low dielectric loss and high breakdown field strength, while maintaining good flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of dielectric energy storage of polymer films, and in particular to a sandwich structure P (VDF-CTFE) composite film and a preparation method thereof. Background Art

[0002] New dielectric materials with low loss and high energy storage density have important application prospects in high-end electronic devices, pulse capacitors, and new energy vehicles. Polyvinylidene fluoride-based polymers have a variety of easily controllable crystal forms. Their all-trans crystal configuration β phase provides strong ferroelectricity, which provides advantages for charge storage and transfer. It has a high dielectric constant (>10) and is widely used by researchers at home and abroad to construct high-energy density polymer energy storage films. For linear dielectrics, the energy density is given by the formula U e =1 / 2ε0ε r E 2 ε0 represents the vacuum dielectric constant of 8.854×10 -12 , ε r It can be seen that the main way to improve energy density is to improve the dielectric constant and breakdown strength of dielectric materials. e It is proportional to the square of the breakdown strength E, so improving the breakdown strength is a more effective way to increase the energy density. At present, the more common and effective way to increase the dielectric constant is to add high dielectric constant inorganic nanoparticles, such as inorganic nano ferroelectric ceramic particles BaTiO3, Ba 0.6 Sr 0.4 TiO3, inorganic nanoparticles ZnO, etc. can greatly improve the dielectric constant of composite materials. However, due to the huge difference in dielectric properties between nanoparticles and polymer matrix, the prepared composite materials often cause the concentration of electric field at the interface, resulting in the composite materials being easily broken down under high electric fields. At the same time, the agglomeration of high-content inorganic nanoparticles will weaken the toughness, mechanical properties, and ease of processing of polymer-based composite materials, affecting their wide range of use properties. Therefore, the development of a polymer film capacitor with both high dielectric constant and high breakdown field strength at low filler content is the main research direction of researchers. Summary of the invention

[0003] The present invention aims to provide a sandwich structure P (VDF-CTFE) composite film and a preparation method thereof.

[0004] In a first aspect, the present application provides a sandwich structure P (VDF-CTFE) composite film, which includes two BNNSs / P (VDF-CTFE) film layers and a PMMA layer sandwiched between the two;

[0005] In the BNNSs / P(VDF-CTFE) film layer, the copolymer HBPE-g-PMMA is adsorbed on the surface of the BNNSs by electrostatic force, and the BNNSs are uniformly dispersed in the P(VDF-CTFE) and arranged in an orientation; the mass ratio of the BNNSs to the P(VDF-CTFE) is 0.1-1wt%;

[0006] The thickness of the BNNSs / P (VDF-CTFE) film layer is between 5 and 20 μm, and the thickness of the PMMA layer is between 0.5 and 5 μm.

[0007] In the BNNSs / P(VDF-CTFE) film layer of the present invention, the surface of the BNNSs is adsorbed with the copolymer HBPE-g-PMMA by electrostatic force. Since the PMMA segment and the PVDF segment have excellent compatibility, the BNNSs are uniformly dispersed in the PVDF matrix and form a strongly interactive interface; and the BNNSs are oriented in the P(VDF-CTFE), and the meaning of the "oriented arrangement" is that the polymer material P(VDF-CTFE) is stretched in one direction, and the molecular chain and the filler BNNSs tend to be arranged in parallel along the stretching direction. Due to the intrinsic high-bandgap of the boron nitride nanosheet, the film has a high breakdown strength, and the BNNSs / P(VDF-CTFE) film provides enhanced interface polarization, significantly improves its dielectric properties, and enhances the energy density of the composite material. The PMMA layer sandwiched between the two BNNSs / P(VDF-CTFE) film layers can effectively delay the electrical breakdown under high voltage due to its good electrical insulation, and improve the dielectric properties of the sandwich structure as a whole.

[0008] In the sandwich structure composite film of the present invention, the relative content F(β) of the β phase crystal in the polymer P(VDF-CTFE) is greater than 60%.

[0009] Preferably, the sandwich structure P (VDF-CTFE) composite film consists of two BNNSs / P (VDF-CTFE) film layers and a PMMA layer sandwiched therebetween.

[0010] In a second aspect, the present application provides a method for preparing a sandwich structure P (VDF-CTFE) composite film, which comprises the following steps:

[0011] (1) mixing a P(VDF-CTFE) solution with a boron nitride nanosheet dispersion to form a uniform casting solution, wherein the mass ratio of BNNSs to P(VDF-CTFE) is 0.1-1wt%; uniformly casting the casting solution onto a flat glass sheet, and then drying to form a film, and after the solvent is completely evaporated and the temperature is reduced to room temperature, a BNNSs / P(VDF-CTFE) thin film layer is obtained;

[0012] (2) casting a layer of PMMA polymer solution on the BNNSs / P(VDF-CTFE) film layer obtained in step (1), drying to form a film, and tearing off the double-layer film on the glass sheet and saving it for later use;

[0013] (3) stacking the BNNSs / P(VDF-CTFE) film layer obtained in step (1) and the double-layer film prepared in step (2) together, and hot pressing to obtain a "sandwich" structure composite film with a PMMA layer as the middle layer;

[0014] (4) The "sandwich" structure composite film obtained in step (3) is uniaxially stretched to orient the BNNSs in P (VDF-CTFE) to obtain a sandwich structure P (VDF-CTFE) composite film.

[0015] In the present invention, the boron nitride nanosheets BNNSs are obtained by liquid-phase exfoliation of hexagonal boron nitride (h-BN) and non-covalent modification of boron nitride nanosheets using HBPE-g-PMMA. The hexagonal boron nitride crystals are purchased from the market, and the lateral size is about 1 μm. The HBPE-g-PMMA is hyperbranched polyethylene grafted polymethylmethacrylate (HBPE-g-PMMA), which is synthesized in the laboratory, and the specific synthesis steps are as follows:

[0016] (a) Under a certain ethylene pressure, HBPE@Br macroinitiator was synthesized by chain walking mechanism using ethylene and 2-(2-bromoisobutyryloxy)ethyl acrylate (BIEA) with Pd-diimine as catalyst.

[0017] (b) HBPE-g-PMMA was synthesized by atom transfer radical polymerization (ATRP) of CuBr and PMDETA at 90 °C in toluene solvent using HBPE@Br as the macroinitiator and MMA as the monomer.

[0018] The preparation method of the boron nitride nanosheets of the present invention is specifically as follows: pouring an organic solvent containing HBPE-g-PMMA polymer into a glass bottle containing a certain amount of hexagonal boron nitride powder, sealing the bottle cap with a film, placing it in an ultrasonic pool for ultrasonication at room temperature for 8 to 72 hours, the ultrasonic power can be selected to be 100 to 320W, taking out the mixed solution after the ultrasonication is completed and putting it into a centrifuge tube for centrifugation, the speed can be controlled at 1000 to 5000rpm, the centrifugation process is mainly to remove the blocky unpeeled hexagonal boron nitride, taking the supernatant for further centrifugation, the speed can be controlled at 6000 to 10000rpm, the main purpose is to remove the excess HBPE-g-PMMA polymer, and the supernatant obtained by centrifugation is the obtained boron nitride nanosheet dispersion. Preferably, the mass ratio of HBPE-g-PMMA to hexagonal boron nitride crystals is 1:2-3, and the organic solvent can be selected from one or more of chloroform, toluene, N-methylpyrrolidone, and N,N-dimethylformamide.

[0019] In the above-mentioned preparation scheme of boron nitride nanosheets, hexagonal boron nitride crystals are exfoliated into BNNSs in an organic solvent with the assistance of HBPE-g-PMMA. This method cleverly utilizes the fact that HBPE-g-PMMA can exfoliate h-BN in a solvent to obtain BNNSs, and HBPE-g-PMMA is adsorbed on the surface of BNNSs through CH-π electrostatic interaction to prevent BNNSs from agglomerating.

[0020] In the present invention, the P(VDF-CTFE) and PMMA polymers can be commercially available products or prepared by themselves according to methods reported in literature.

[0021] In step (1) of the present invention, the solvent of the P(VDF-CTFE) solution may be DMF, NMP or DMAc. Preferably, the solvent of the P(VDF-CTFE) solution is the same as the solvent of the boron nitride nanosheet dispersion, such as DMF. The thickness of the BNNSs / P(VDF-CTFE) film layer is achieved by controlling the concentration and volume of the casting solution. Preferably, the concentration of P(VDF-CTFE) in the casting solution is 15 to 20 mg / mL, so that the casting solution carried on each piece of glass is 3 to 5 mL / 20 cm 2 , more preferably 4mL / 20cm 2 .

[0022] In steps (1) and (2) of the present invention, the drying conditions for film formation are preferably: drying at 60-100° C. for 4-10 hours.

[0023] In step (2) of the present invention, the solvent of the PMMA polymer solution can be selected from chloroform, toluene, N,N-dimethylformamide, preferably CHCl3. The thickness of the PMMA layer is achieved by controlling the concentration and volume of the PMMA polymer solution. Preferably, the concentration of the PMMA polymer solution is 5 to 20 mg / mL, and the volume is 2 to 3 mL / 20 cm based on the area of ​​the BNNSs / P (VDF-CTFE) film layer. 2 , more preferably 2mL / 20cm 2 .

[0024] In step (3) of the present invention, the temperature during the hot pressing process can be controlled to be 160-200° C., the pressure to be 8-15 MPa, and the hot pressing time to be 10-20 min.

[0025] In step (4) of the present invention, the uniaxial stretching is specifically carried out as follows: the film is subjected to constant temperature treatment at 80-120° C. for 5-15 min in an oven of a tensile machine, and is uniaxially stretched to 2-5 times of the original length at a stretching rate of 10-100 mm / min to obtain a sandwich structure P (VDF-CTFE) composite film. Preferably, the stretching rate is 20 mm / min, and the film is stretched to 4 times of the original length.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention obtains boron nitride nanosheets by liquid phase exfoliation of hyperbranched polyethylene grafted with polymethyl methacrylate in a general organic solvent. At the same time, the interaction between the hyperbranched structure and the surface of the nanosheet allows the target polymer to be adsorbed on the surface of the nanosheet, playing the role of surface modified filler. The filler has good dispersion in the polymer matrix and strong interfacial interaction.

[0028] (2) The present invention prepares a sandwich structure composite film by hot pressing and stretching, wherein the upper and lower layers are BNNSs / P (VDF-CTFE) nanocomposite layers, and the nanofillers are oriented during the stretching process, thereby improving the polarization performance of the sandwich structure; PMMA is used as the middle layer, and its good electrical insulation effectively blocks the development of electrical dendrites under high voltage, thereby improving the high voltage resistance of the sandwich structure. The experimental results show that the sandwich structure composite film of the present invention has lower dielectric loss at high frequencies than the two-layer structure composite film without the PMMA middle layer.

[0029] The nano composite material prepared by the invention has a higher dielectric constant, low dielectric loss and high breakdown field strength, while maintaining good flexibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the composite film preparation process;

[0031] Figure 2 is the infrared spectrum of the prepared composite film material;

[0032] Figure 3 The content of β phase in composite films with different PMMA contents;

[0033] Figure 4 is the dielectric constant of P(VDF-CTFE) composites with different PMMA contents in the middle layer;

[0034] Figure 5 is the dielectric loss of P(VDF-CTFE) composites with different PMMA contents in the middle layer;

[0035] Figure 6 The dielectric constant and dielectric loss diagram of the three-layer structure with different BNNSs contents in the upper and lower layers;

[0036] Figure 7 The dielectric constant and dielectric loss diagram of the three-layer structure at different stretching rates;

[0037] Figure 8 The dielectric constant and dielectric loss diagram of the three-layer structure at different stretching ratios. DETAILED DESCRIPTION

[0038] Specific embodiments are given below to further illustrate the technical solution of the present invention. However, it is worth noting that the following embodiments cannot be understood as limiting the scope of protection of the present invention. Technical personnel skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the content of the above invention, which still fall within the scope of protection of the present invention.

[0039] Embodiment 0

[0040] The HBPE-g-PMMA is hyperbranched polyethylene grafted polymethyl methacrylate (HBPE-g-PMMA for short), which is synthesized in the laboratory. The specific synthesis steps are as follows:

[0041] (1) Take a clean and strictly dried 100 mL Schlenk bottle and add 342 mmol of MMA monomer, 12 mL of anhydrous toluene, 0.38 mmol of HBPE@Br and 0.76 mmol of PMDETA in proportion.

[0042] (2) The mixed solution was frozen, vacuumed, and thawed three times to ensure an anhydrous and oxygen-free environment during the polymerization process. Then, 0.38 mmol of CuBr was quickly added under a nitrogen atmosphere, and the mixture was sealed and reacted at 90° C. for 12 h.

[0043] (3) After the reaction has proceeded for a predetermined time, the reaction flask is immersed in an ice-water bath to terminate the reaction, and then the solution is blown dry with cold air, THF is added to dissolve the product, and methanol is continuously added dropwise to precipitate the product, and finally the supernatant is poured out. This step is repeated three times to purify the product.

[0044] (4) The above product was transferred into a centrifuge tube and dried in a vacuum oven at 60° C. for 24 h to obtain a white solid powder, namely HBPE-g-PMMA.

[0045] Example 1

[0046] Step 1: Weigh 0.1g of HBPE-g-PMMA into a glass bottle, add 10mL of DMF, stir to assist the copolymer HBPE-g-PMMA to fully dissolve, then add 0.24g of hexagonal boron nitride (h-BN) powder into the glass bottle, and finally add 50mL of DMF (the mass of h-BN in the solvent is recorded as 4mg / mL), and seal the bottle cap.

[0047] Step 2: Place the mixed solution treated in step 1 in a water bath ultrasonic bath at room temperature for 48 hours, and select an ultrasonic power of 240W.

[0048] Step 3: Take out the mixed solution after ultrasonic treatment in step 2 and put it into a centrifuge tube, centrifuge it at 3000 rpm for 30 minutes to mainly remove the unpeeled block h-BN. Then take the supernatant and save it, which is the dispersion of boron nitride nanosheets (BNNSs).

[0049] Step 4: Take 40 mL of the dispersion in step 3, centrifuge at 7000 rpm for 30 min in a centrifuge, the main purpose is to remove excess HBPE-g-PMMA polymer, take out the upper layer, collect the bottom product and dry it in a vacuum oven to constant weight, which is BNNSs, of which HBPE-g-PMMA accounts for 19.6% of the mass of BNNSs. Then add DMF (the mass of BNNSs in the solvent is recorded as 1 mg / mL), and re-ultrasonicate and disperse for 2 h for standby use.

[0050] Step 5: Dissolve 200 mg of P(VDF-CTFE) powder in 10 mL of DMF and stir magnetically until the solution is transparent and uniform. Then add 1 mL of 1 mg / mL BNNSs dispersion. After the mixture is stirred magnetically, take 4 mL of the mixture and cast it on a 4×5 cm glass slide in a blast drying oven. Evaporate the solvent at 60°C to form a film. After 8 hours, peel off the film, which is recorded as BNNSs / P(VDF-CTFE) composite film with a thickness of 20 μm.

[0051] Step 6: Dissolve 0.05g PMMA in 10mL CHCl3, and let stand until PMMA is fully dissolved. Repeat step 5, and after the mixed solution is cast on a glass slide and the solvent evaporated for 2 hours, the BNNSs / P(VDF-CTFE) has basically formed a film. Then take 2mL of the above PMMA solution, use a dropper to evenly cast a layer of PMMA polymer solution on the BNNSs / P(VDF-CTFE) composite film, continue to evaporate the solvent at 60°C to form a film, and peel off the film after 8 hours to prepare a two-layer composite film with a BNNSs / P(VDF-CTFE) composite film layer and a PMMA layer, with a thickness of 25μm.

[0052] The PMMA is from Shanghai Jingqi Polymer Materials Co., Ltd., and its weight average molecular weight is w =63650.

[0053] Step 7: Place the two-layer composite film structure prepared in step 6 on the lower layer, and the single-layer film prepared in step 5 on the upper layer, with a 0.2 mm thick high-temperature resistant PET film as the molded isolation layer, and hot press it into a three-layer film under a tablet press, with the hot pressing temperature set to 170°C, the pressure to 11 MPa, and the time to 15 min. The composite film peeled off from the isolation layer is a three-layer structure with BNNSs / P (VDF-CTFE) composite films on the upper and lower layers and PMMA in the middle layer.

[0054] Step 8: Cut the composite film of the "sandwich" structure prepared by hot pressing in step 7 into strips with a length of 3 cm and a width of 1 cm, load the strips onto the film fixture, keep the temperature at 100°C for 10 minutes in the oven of the tensile machine, and uniaxially stretch it to 4 times the original length at a stretching rate of 20 mm / min to obtain a stretched strip. The stretched sample film is the prepared three-layer composite material, which has a high dielectric constant and low dielectric loss, and has good processability.

[0055] Embodiment 2-4

[0056] The mass of PMMA in step six of Example 1 was changed to 0.1 g (Example 2), 0.15 g (Example 3), and 0.2 g (Example 4) PMMA dissolved in 10 mL CHCl3, and other conditions remained unchanged to prepare a three-layer composite membrane material.

[0057] The schematic diagram of the preparation process of the composite membrane material is as follows Figure 1 As shown, from Figure 1 It can be seen that the three-layer composite film has good toughness. Figure 2 is the infrared spectrum of the composite film. Figure 3is the relative content of β phase calculated by Lambert-Beer law. It can be seen that in the two-layer structure without PMMA layer in the middle, F(β)=31.8%. As the content of PMMA in the middle increases, when the mass of PMMA in the middle is 10 mg, the content of β phase increases to a maximum of 97%. Then the content of β phase decreases slowly, but it is generally higher than the β phase content of the two-layer composite film. At the same time, the frequency-dependent dielectric constant and dielectric loss are measured at room temperature. Figure 4 and Figure 5 shown.

[0058] Characterization and testing

[0059] The composite film material is coated with a 1-3 μm thick conductive silver layer as an electrode with an area of ​​about 1 cm 2 The frequency-dependent capacitance and loss angle were tested using a precision impedance analyzer (4294ALCR, Agilent, USA) over a frequency range of 10 2 ~10 7 Hz, calculate the dielectric constant and dielectric loss of each composite material.

[0060] Test results comparison and analysis

[0061] from Figure 2 It can be seen that the absorption peak of the polar β phase of P(VDF-CTFE) in the three-layer composite film is obvious, indicating that the composite film has been stretched, inducing the transformation of P(VDF-CTFE) from α to β crystal form, which is beneficial to the improvement of the dielectric constant. At the same time, the absorption peaks of C=O and CO from the middle layer PMMA appeared in the three-layer composite film.

[0062] Figure 4 It can be seen that at the same frequency, as the PMMA content in the middle layer increases, the dielectric constant of the composite film also decreases. However, the overall decrease is not much, and the composite film with the least PMMA middle layer content has the highest dielectric constant. This shows that the insulating layer of the middle PMMA can effectively prevent the migration of carriers and prevent the dielectric from breaking down prematurely under high fields due to charge concentration.

[0063] Figure 5 It can be seen from the dielectric loss that at low frequencies, the dielectric loss angles of the three-layer composite film and the two-layer composite film are all below 0.05, indicating that the structural design maintains a high dielectric constant while also maintaining low dielectric loss. 6 ~10 7 Hz, with the addition of the PMMA layer, the dielectric relaxation of the composite film gradually weakened, which significantly suppressed the loss at high frequencies.

[0064] Embodiment 5-9

[0065] The amounts of BNNSs added in step five of Example 1 were respectively changed to 0wt% (Example 5), 0.1wt% (Example 6), 0.3wt% (Example 7), 0.8wt% (Example 8), and 1.0wt% (Example 9), while other conditions remained unchanged, to prepare a three-layer composite membrane material.

[0066] from Figure 6 It can be seen that with the increase of BNNSs content in the upper and lower layers of BNNSs / P(VDF-CTFE), the dielectric constant first increases and then decreases; at the same time, its dielectric loss increases from 10 3 Hz is below 0.05, effectively maintaining the properties of high dielectric and low loss.

[0067] Examples 10-13

[0068] The stretching rate in step eight in Example 1 was changed to 10 mm / min (Example 10), 30 mm / min (Example 11), 40 mm / min (Example 12), and 50 mm / min (Example 13), and other conditions remained unchanged to prepare a three-layer composite membrane material.

[0069] from Figure 7 It can be seen that the dielectric constant shows a downward trend with the increase of stretching rate, but the overall decrease is not obvious; its dielectric loss is also maintained at a low level.

[0070] Examples 14-17

[0071] The stretching ratio in step eight in Example 1 was changed to 0 times (Example 14), 2 times (Example 15), 3 times (Example 16), and 5 times (Example 17), and other conditions remained unchanged to prepare a three-layer composite film material.

[0072] Figure 8 The dielectric properties of the three-layer composite film at different stretching ratios are described in Figure 2. From the analysis of the figure, compared with the unstretched composite film, the dielectric constant of the three-layer composite film increases from 17 to about 29, while the dielectric loss is at a lower level, indicating that stretching can significantly improve the dielectric properties of the composite film.

[0073] Comparative Example 1

[0074] Step 1: Weigh 0.1g of HBPE-g-PMMA into a glass bottle, add 10mL of DMF, stir to assist the copolymer HBPE-g-PMMA to fully dissolve, then add 0.24g of hexagonal boron nitride powder into the glass bottle, and finally add 50mL of DMF (the mass of h-BN in the solvent is recorded as 4mg / mL), and seal the bottle cap.

[0075] Step 2: Place the mixed solution treated in step 1 in a water bath ultrasonic bath at room temperature for 48 hours, and select an ultrasonic power of 240W.

[0076] Step 3: Take out the mixed solution after ultrasonic treatment in step 2 and put it into a centrifuge tube, centrifuge it at 3000 rpm for 30 minutes to mainly remove the unpeeled block h-BN. Then take the supernatant and save it, which is the dispersion of boron nitride nanosheets.

[0077] Step 4: Take 40 mL of the dispersion in step 3 and centrifuge it at 7000 rpm for 30 min. The main purpose is to remove the excess HBPE-g-PMMA polymer. Pour out the upper layer, collect the bottom product and dry it in a vacuum oven to constant weight, which is boron nitride nanosheets (BNNSs). Then add DMF (the mass of BNNSs in the solvent is recorded as 1 mg / mL) and re-ultrasonicate and disperse for 2 h.

[0078] Step 5: Dissolve 200 mg of P(VDF-CTFE) powder in 10 mL of DMF and stir magnetically until the solution is uniform and transparent. Then add 1 mg / mL of BNNSs dispersion (containing 1 mg of BNNSs). After the mixture is stirred magnetically, take 4 mL of the mixture and cast it on a 4×5 cm glass slide in a blast drying oven. Evaporate the solvent at 60°C to form a film. After 8 hours, peel off the film, which is recorded as BNNSs / P(VDF-CTFE) composite film.

[0079] Step 6: Stack two composite films prepared in step 5, use a 0.2 mm thick high temperature resistant PET film as a molded isolation layer, and heat press them into two layers of film under a sheet press. The heat pressing temperature is set to 170°C, the pressure is 11 MPa, and the time is 15 minutes. Peel off the upper and lower layers of the composite film, which are both BNNSs / P(VDF-CTFE), from the isolation layer.

[0080] Step 7: Cut the two-layer BNNSs / P (VDF-CTFE) composite film prepared by hot pressing in step 6 into a strip with a length of 3 cm and a width of 1 cm, load the strip onto a film fixture, keep the strip in an oven of a tensile machine at 80°C for 10 min, and uniaxially stretch it to 4 times its original length at a stretching rate of 20 mm / min to obtain a stretched strip. The stretched sample film is a two-layer composite material.

Claims

1. A sandwich structure P (VDF-CTFE) composite film, which includes two BNNSs / P (VDF-CTFE) film layers and a PMMA layer sandwiched between the two; In the BNNSs / P(VDF-CTFE) film layer, the copolymer HBPE-g-PMMA is adsorbed on the surface of the BNNSs by electrostatic force, and the BNNSs are uniformly dispersed in the P(VDF-CTFE) and arranged in an orientation; the mass ratio of the BNNSs to the P(VDF-CTFE) is 0.1-1wt%; The thickness of the BNNSs / P(VDF-CTFE) film layer is between 5 and 20 μm, and the thickness of the PMMA layer is between 0.5 and 5 μm; The method for preparing the sandwich structure P (VDF-CTFE) composite film comprises the following steps: (1) mixing a P(VDF-CTFE) solution with a boron nitride nanosheet dispersion to form a uniform casting solution, wherein the mass ratio of BNNSs to P(VDF-CTFE) is 0.1-1wt%:1; casting the casting solution uniformly onto a flat glass sheet, and then drying to form a film, and after the solvent is completely evaporated and the temperature is reduced to room temperature, a BNNSs / P(VDF-CTFE) thin film layer is obtained; (2) casting a layer of PMMA polymer solution on the BNNSs / P(VDF-CTFE) film layer obtained in step (1), drying to form a film, and tearing off the double-layer film on the glass sheet and saving it for later use; (3) stacking the BNNSs / P(VDF-CTFE) film layer obtained in step (1) and the double-layer film prepared in step (2) together, and hot pressing to obtain a "sandwich" structure composite film with a PMMA layer as the middle layer; wherein the temperature during the hot pressing process is controlled to be 160-200° C., the pressure is 8-15 MPa, and the hot pressing time is 10-20 min; (4) The "sandwich" structure composite film obtained in step (3) is uniaxially stretched to orient the BNNSs in the P(VDF-CTFE) to obtain a sandwich structure P(VDF-CTFE) composite film, wherein the relative content F(β) of the β phase crystal in the polymer P(VDF-CTFE) is greater than 60%.

2. The sandwich structure P (VDF-CTFE) composite film according to claim 1, characterized in that: The sandwich structure P (VDF-CTFE) composite film consists of two BNNSs / P (VDF-CTFE) film layers and a PMMA layer sandwiched between the two.

3. A method for preparing the sandwich structure P (VDF-CTFE) composite film according to claim 1, comprising the following steps: (1) mixing a P(VDF-CTFE) solution with a boron nitride nanosheet dispersion to form a uniform casting solution, wherein the mass ratio of BNNSs to P(VDF-CTFE) is 0.1-1wt%:1; casting the casting solution uniformly onto a flat glass sheet, and then drying to form a film, and after the solvent is completely evaporated and the temperature is reduced to room temperature, a BNNSs / P(VDF-CTFE) thin film layer is obtained; (2) casting a layer of PMMA polymer solution on the BNNSs / P(VDF-CTFE) film layer obtained in step (1), drying to form a film, and tearing off the double-layer film on the glass sheet and saving it for later use; (3) stacking the BNNSs / P(VDF-CTFE) film layer obtained in step (1) and the double-layer film prepared in step (2) together, and hot pressing to obtain a "sandwich" structure composite film with a PMMA layer as the middle layer; wherein the temperature during the hot pressing process is controlled to be 160-200° C., the pressure is 8-15 MPa, and the hot pressing time is 10-20 min; (4) The "sandwich" structure composite film obtained in step (3) is uniaxially stretched to orient the BNNSs in the P(VDF-CTFE) to obtain a sandwich structure P(VDF-CTFE) composite film, wherein the relative content F(β) of the β phase crystal in the polymer P(VDF-CTFE) is greater than 60%.

4. The preparation method according to claim 3, characterized in that: The preparation method of the boron nitride nanosheets is specifically as follows: pouring an organic solvent containing HBPE-g-PMMA polymer into a glass bottle containing a certain amount of hexagonal boron nitride powder, sealing the bottle cap with a film, placing the bottle in an ultrasonic tank for ultrasonic treatment at room temperature for 8 to 72 hours, selecting an ultrasonic power of 100 to 320 W, taking out the mixed solution after the ultrasonic treatment, placing it in a centrifuge tube for centrifugation, controlling the speed at 1000 to 5000 rpm, taking the supernatant for further centrifugation, controlling the speed at 6000 to 10000 rpm, and the supernatant obtained by centrifugation is the obtained boron nitride nanosheet dispersion; wherein the feed mass ratio of HBPE-g-PMMA to hexagonal boron nitride crystals is 1:2-3, and the organic solvent is selected from one or more of chloroform, toluene, N-methylpyrrolidone, and N,N-dimethylformamide.

5. The preparation method according to claim 3, characterized in that: In step (1), the solvent of the P(VDF-CTFE) solution is DMF, NMP or DMAc; the concentration of P(VDF-CTFE) in the casting solution is 15-20 mg / mL, so that the casting solution carried on each piece of glass is 3-5 mL / 20 cm 2 .

6. The preparation method according to claim 3, characterized in that: In steps (1) and (2), the drying conditions for film formation are: drying at 60-100° C. for 4-10 hours.

7. The preparation method according to claim 3, characterized in that: In step (2), the solvent of the PMMA polymer solution is selected from chloroform, toluene or N,N-dimethylformamide; the concentration of the PMMA polymer solution is 5-20 mg / mL, and the volume usage is 2-3 mL / 20 cm based on the area of ​​the BNNSs / P(VDF-CTFE) film layer. 2 .

8. The preparation method according to claim 3, characterized in that: In step (4), the uniaxial stretching is specifically implemented as follows: constant temperature treatment at 80-120°C in an oven of a tensile testing machine for 5-15 min, uniaxial stretching at a stretching rate of 10-100 mm / min to 2-5 times the original length, to obtain a three-layer composite film.

9. The preparation method according to claim 8, characterized in that: In step (4), the stretching rate is 20 mm / min, and the film is stretched to 4 times its original length.

Citation Information

Patent Citations

  • Dielectric composite material

    CN105219021A

  • All-polymer multilayered composite material and preparation method and application thereof

    CN110070991A